THE ROLE OF THE COMMUNITY LEARNING ACTIVITY CENTER (PKBM) IN THE DEVELOPMENT OF FRUIT AND ORNAMENTAL PLANT FARMERS THROUGH TRAINING - Ganda Sasmita (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
The background of this research is that in 2019 agriculture becomes one of the commodities which is expected to continue to increase in order to be able to export to various countries, but farmers in Parongpong still have many obstacles, one of which is constraints related to production results with the lack of marketing networks for the products they produce. The research objective is to find out how the role of PKBM in the development of fruit and ornamental plant farmers through training. The theory used in this research is PKBM theory and training theory.Researchers used interview and observation techniques with qualitative descriptive methods with qualitative approaches to obtain information from informants. The sample in this study was a PKBM manager, one tutor, and three randomly selected trainees (farmers). The result of the research is that the PKBM Suka Baru is carrying out its role through one of the programs, namely training for farmers of ornamental plants and fruit that are around the PKBM Suka Baru. As for the results of the training received by farmers while participating in training, it should continue to be evaluated and monitored so that farmers can continue to control their development. The conclusion is that the Suka Baru PKBM has carried out the PKBM role as it should through a development training program for fruit and ornamental plant farmers. This role was seen from the Suka Baru PKBM activities trying to improve the welfare of the lives of the people belonging to the poor and underdeveloped categories. The role of PKBM is also aimed at improving the welfare of every targeted citizen. Latarbelakang penelitian ini adalah adalah Bidang pertanian di tahun 2019 menjadi salah satu komoditi yang di harapakan dapat terus meningkat agar dapat mengekspor ke berbagai Negara akan tetapi para petani di Parongpong masih banyak kendala salah satunya kendala terkait hasil produksi dengan masih minimnya jaringan pemasaran  atas produk yang dihasilkannya Tujuan penelitian adalah untuk mengetahui bagaimana peran PKBM dalam rangka pengembangan petani tanaman buah dan tanaman hias melalui pelatihan. Teori yang digunakan dalam penelitian ini adalah teori PKBM dan teori pelatihan. Peneliti menggunakan teknik wawancara dan observasi dengan metode deskriptif kualitatif dengan pendekatan kualitatif untuk mendapatkan informasi dari narasumber. Sampel dalam penelitian ini adalah seorang pengelola PKBM, Satu orang tutor, dan tiga orang peserta pelatihan (petani) yang dipilih secara random. Hasil penelitian adalah PKBM Suka Baru menjalankan peranannya melalui salah satu program yaitu pelatihan untuk para petani tanaman hias dan buah yang ada di sekitar PKBM Suka Baru. Sedangkan untuk hasil pelatihan yang di dapatkan oleh para petani selama mengikuti pelatiha sebaiknya terus dilakukan evaluasi dan pengawasan agar para petani bisa terus terkontrol pengembangan dirinya. Kesimpulannya adalah PKBM Suka Baru sudah menjalankan peran PKBM sebagaimana mestinya melalui sebuah program pelatihan pengembangan untuk petani tanaman buah dan tanaman hias, peranan tersebut dilihat dari kegiatan PKBM Suka Baru berusaha meningkatkan kesejahteraan hidup warga masyarakat yang termasuk kategori miskin dan terbelakang. Peranan PKBM juga bertujuan meningkatkan kesejahteraan setiap warga masyarakat yang menjadi sasaran.